Association of the Low Pregnancy-Associated Plasma Protein A and Pregnancy Complications in the First Trimester: A Prospective Cohort Study - Abtahian, Ameneh; Fakhredin, Hanieh; Darvish, Soodabeh (Student Research in Translational Medicine, 2020)
Background and Aims: This study aimed to assess the association between the low maternal serum of pregnancy-associated plasma protein-A (PAPP-A) during the first trimester and pregnancy outcomes. Materials and Methods: We conducted a prospective cohort study of 118 pregnant women undergoing first-trimester screening between 2016 and 2017 at Taleghani and Imam Hussein hospital in Tehran, Iran. We recorded demographic data and blood samples were to analyze the value of PAPP-A, based on which we divided the participants into two groups: PAPP-A>10 percentile as a control group and PAPP-A≤10th percentile as a study group. The pregnancies underwent follow-up observations for obstetric complications during pregnancy. Chi-square or Fisher exact test and Mann-Whitney U test were applied to analyze data by SPSS 26. Results: In this study,118 pregnant women were enrolled. Our results show a significant association between low PAPP-A (<10th percentile) and preterm labor, small for gestational age (SGA), hypertension, preeclampsia (P<0.05), but no statistically significant difference was found between low PAPP-A and stillbirth. Demographic data, including age, gravida, parity, BMI, had no relationship with low PAPP-A, significantly (P>0.05). Conclusion: Low PAPP-A is associated with adverse outcomes; thus, measuring the PAPP-A within the first trimester is suggested for timely management.